Clinical impact of the alpha-galactosidase A gene single nucleotide polymorphism -10C>T: A single-center observational study. Issue 21 (May 2018) - Oder, Daniel; Liu, Dan; Üçeyler, Nurcan; Sommer, Claudia; Hu, Kai; Salinger, Tim; Müntze, Jonas; Petritsch, Bernhard; Ertl, Georg; Wanner, Christoph; Nordbeck, Peter; Weidemann, Frank
Abstract : Abstract: Single nucleotide polymorphisms (SNPs) in the alpha-galactosidase A gene region (GLA) have been discussed as potential cause of symptoms and organ manifestations similarly to those seen in Fabry disease (FD). However, due to scarce data, clinical implications remain limited. The aim of the present study was to investigate the clinical impact of -10C>T SNP in the GLA. Prospective single-center observational study to determine the natural history and outcome of FD. Subjects initially referred to the Fabry Center for Interdisciplinary Therapy Würzburg (FAZIT) for management of suspected FD (11 women, 2 men, mean age 42 ± 10 years) who were tested negative for coding GLA mutations but positive for the noncoding -10C>T SNP underwent comprehensive characterization for therapy recommendation. All subjects reported at least 1 neurological, but no cardiac or renal symptoms. In 7 patients, pain of unknown etiology was reported and 3 patients had a history of cryptogenic stroke. In all patients, α-GAL activity was at a lower limit, ranging between 0.27 and 0.45 nmol/min per mg protein (reference: 0.4–1.0), while plasma Lyso-Gb3 levels remained normal (range 0.39 ± 0.33; reference: ⩽0.9 ng/mL). For both hemizygous subjects investigated, brain magnetic resonance imaging revealed unspecific white matter lesions. One of these subjects had suffered from severe early-onset stroke, the other showed mild hypertrophic cardiomyopathy. Presence of isolated heterozygous -10C >T SNP is not associated with clinically relevant symptoms or organ manifestations as seen in FD. Respective polymorphisms might, however, play a role in modifying disease severity in FD. Great care has to be taken in respective subjects suspected to suffer from nonclassical FD in order to prevent unnecessary Fabry-specific therapy.